Nurses and Patient Safety: A Literature Review Study - Seriga, Seriga; Hassan, Hafizah Che; Sansuwito, Tukimin (International Journal of Health Sciences, 2024)
Patient safety is a global issue, especially when patients are in hospitals. The implementation of patient safety in hospitals requires the role of nurses as the most dominant health workers and directly meet patients for 24 hours, therefore it is necessary to see the extent of the role of nurses in preventing patient safety incidents. The purpose of this study was to identify the results of research on the implementation of patient safety by nurses in hospitals. The method used is a literature review, using an electronic database identified from Pubmed, Google Scholar, Google and Gray literature (National Library of Indonesia) with keywords: patient safety, compliance, implementation of patient safety by nurses. The inclusion criteria in this study were the implementation of patient safety carried out by nurses, the research design was qualitative and quantitative, the study used quantitative or qualitative methods, empirical papers in English or Indonesian published between 2018-2020. The articles collected were nine papers which were synthesized narratively. The results found four papers on the implementation of patient safety, one paper on the use of surgical safety checklist, two papers on reducing the risk of infection, one paper on handover and one paper on reducing the risk of falls. The results of this literature review found various innovations carried out by nurses in implementing patient safety in hospitals. These innovations can be used as a reference for hospitals as innovations in improving the quality of service that prioritizes patient safety as an aspect of patient satisfaction while in the hospital.